Utilização de rejeitos da mineração de ferro e fontes alternativas de carbono para a obtenção de biocombustíveis - Vivian Andrade Luciano (2023)
Advances of the activities of the mining industries and the increased demand of operations have caused the amount of waste generated by these sectors to increase more and more. The iron mining segment is one of the most important in the country and is responsible for the generation of large amounts of tailings. Thus, the reuse of these wastes is an interesting alternative to reduce the need to store this material. Iron mining tailings are rich in iron oxides and quarts and can be used for different applications such as the production of biofuels. Therefore, this work had, as general objective, to use iron mining tailings as a source of iron for the production of high added value products using oleic acid and residual frying oil as carbon sources. These compounds were produced by thermal decomposition reaction of organic compounds in the presence of the tailings, in a high pressure reactor (12.5 bar), using the ratio of 1:1 in mass of acid or oil in relation to the tailings, at temperatures between 250 to 450 ° C and time intervals between 3 and 12 hours. These reactions formed solid, liquid and gaseous products, which were characterized by elemental analysis (CNH), XRD, FTIR, TG, 1H and 13C NMR and GC. The results showed that, for all the reactions presented in this work, the solid products obtained showed a percentage of less than 6% of carbon material, which is an advantage to not forming coke in the solid products. In addition, there was the formation of different iron phases in the solids, which changed according to the reaction time and temperature. For the reactions carried out at temperatures of 250 and 350 °C over 3 hours using oleic acid as a carbon source, the main fraction obtained was the liquid. However, it was mainly composed of the starting compound. For the reactions carried out at 400 and 450 °C over 3 hours, the main fraction was gas, being selective for hydrogen gas. For the reaction carried out at 350 °C for 12 hours and using oleic acid as a carbon source, the mass balance showed the formation of similar amounts of liquid and gaseous products. The liquid products were separated by means of a chromatographic column and were selective for ketones, while the gaseous products were identified and presented a greater selectivity for C3 hydrocarbons. The reactions carried out with the residual frying oil as a carbon source presented interesting results. Preliminary characterization results showed that for reactions at 350 °C in time intervals of 3 and 12 hours, similar mass balances were obtained, promoting the formation of a greater quantity of liquid products, which are mainly composed of ketones. Other reactions varying other parameters and other carbon sources will be carried out. However, these results already show the potential of this work, in which iron tailings were used as a source of iron and residual carbon sources were also used, obtaining several interesting products for the industrial sector. Studies of the technical and economic viability of this work were also carried out, from the Escale-se program, which evaluated the necessary steps to carry out the scaling of a technology. In this study, a visual identity was created, a technology business model, evaluating the importance of technology, market conditions, in addition to carrying out mass and energy balances for the process.